GSK3ß‐dependent dysregulation of neurodevelopment in SPG11‐patient induced pluripotent stem cell model. Issue 5 (May 2016) - Mishra, Himanshu K.; Prots, Iryna; Havlicek, Steven; Kohl, Zacharias; Perez‐Branguli, Francesc; Boerstler, Tom; Anneser, Lukas; Minakaki, Georgia; Wend, Holger; Hampl, Martin; Leone, Marina; Brückner, Martina; et al.
Abstract : Objective: Mutations in the spastic paraplegia gene 11 (SPG11), encoding spatacsin, cause the most frequent form of autosomal‐recessive complex hereditary spastic paraplegia (HSP) and juvenile‐onset amyotrophic lateral sclerosis (ALS5). When SPG11 is mutated, patients frequently present with spastic paraparesis, a thin corpus callosum, and cognitive impairment. We previously delineated a neurodegenerative phenotype in neurons of these patients. In the current study, we recapitulated early developmental phenotypes of SPG11 and outlined their cellular and molecular mechanisms in patient‐specific induced pluripotent stem cell (iPSC)‐derived cortical neural progenitor cells (NPCs). Methods: We generated and characterized iPSC‐derived NPCs and neurons from 3 SPG11 patients and 2 age‐matched controls. Results: Gene expression profiling of SPG11‐NPCs revealed widespread transcriptional alterations in neurodevelopmental pathways. These include changes in cell‐cycle, neurogenesis, cortical development pathways, in addition to autophagic deficits. More important, the GSK3ß‐signaling pathway was found to be dysregulated in SPG11‐NPCs. Impaired proliferation of SPG11‐NPCs resulted in a significant diminution in the number of neural cells. The decrease in mitotically active SPG11‐NPCs was rescued by GSK3 modulation. Interpretation: This iPSC‐derived NPC model provides the first evidence for an early neurodevelopmental phenotype in SPG11, with GSK3ß as a potential novel target to reverse the disease phenotype. Ann Neurol 2016;79:826–840